A Current Approach in Nursing Education: Jigsaw Cooperative Learning - Çelik, Hanife; Aktura, Seher Çevik (Bingol University, 2023)
Nursing education plays an important role in the development of nursing professionalism. The Jigsaw Collaborative Learning Method allows students to be involved in course materials, preparations and presentations and encourages peer learning. This technique is done with the support and guidance of instructors. Thus, it activates students' positive attitude instincts. It has also been reported that the use of Jigsaw Cooperative Learning Method in nursing education improves students' critical thinking and interpersonal communication skills, increases their learning attitudes, performance and motivation to learn; Jigsaw Cooperative Learning Method also helps them manage their time and set learning goals. It may be recommended that the Jigsaw Cooperative Learning Method should be included more in theoretical and psychomotor skills training and nursing curricula, used in clinical and laboratory settings, and more research should be conducted on its use in nursing education.

Hemşirelik eğitimi hemşirelik profesyonelliğinin geliştirilmesinde önemli bir rol oynamaktadır. Jigsaw İşbirlikli Öğrenme Yöntemi, öğrencilerin ders materyallerine, hazırlıklarına ve sunumlarına dahil olmalarını sağlar ve akran öğrenmesini teşvik eder. Bu teknik, eğitmenlerin desteği ve rehberliği ile yapılır. Böylece öğrencilerin olumlu tutum içgüdülerini harekete geçirir. Hemşirelik eğitiminde Jigsaw İşbirlikli Öğrenme Yöntemi’nin kullanımının öğrencilerin eleştirel düşünme ve kişilerarası iletişim becerilerini geliştirdiği, öğrenme tutumlarını, performanslarını ve öğrenme motivasyonlarını arttırdığı; Jigsaw İşbirlikli Öğrenme Yöntemi’nin ayrıca zamanlarını yönetmelerine ve öğrenme hedeflerini belirlemelerine yardımcı olduğu da rapor edilmiştir. Jigsaw İşbirlikli Öğrenme Yöntemi’nin teorik ve psikomotor beceri eğitimi ve hemşirelik müfredatlarında daha fazla yer alması, klinik ve laboratuvar ortamlarında kullanılması ve hemşirelik eğitiminde kullanımına ilişkin daha fazla araştırma yapılması önerilebilir.
Hemşirelik Eğitiminde Güncel Bir Yaklaşım: Jigsaw İşbirlikli Öğrenme
Keywords: Fundamentals of Nursing; Hemşirelik Esasları